2014
DOI: 10.1371/journal.pone.0093215
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Gene Expression Profiles of Haemocytes from Schistosome-Susceptible and -Resistant Biomphalaria glabrata Exposed to Schistosoma mansoni Excretory-Secretory Products

Abstract: During its life cycle, the helminth parasite Schistosoma mansoni uses the freshwater snail Biomphalaria glabrata as an intermediate host to reproduce asexually generating cercariae for infection of the human definitive host. Following invasion of the snail, the parasite develops from a miracidium to a mother sporocyst and releases excretory-secretory products (ESPs) that likely influence the outcome of host infection. To better understand molecular interactions between these ESPs and the host snail defence sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
(99 reference statements)
0
20
0
Order By: Relevance
“…Others include gastric intrinsic factor, serine/arginine-rich splicing factor 7 and NRDE-2. These genes also may be useful targets in the treatment of schistosomiasis, and our dataset can in this way act as a bridge between previous functional investigations such as [56] and sequences of presently unknown function in the nr database.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Others include gastric intrinsic factor, serine/arginine-rich splicing factor 7 and NRDE-2. These genes also may be useful targets in the treatment of schistosomiasis, and our dataset can in this way act as a bridge between previous functional investigations such as [56] and sequences of presently unknown function in the nr database.…”
Section: Resultsmentioning
confidence: 90%
“…For example, [56] used a microarray-based method to identify 98 differentially expressed sequences from haemocytes of schistosome-resistant and schistosome-susceptible B. glabrata after exposure to excretory-secretory products from S. mansoni. Of these 98 EST derived sequences, 61 were at that time unable to be assigned homology to known gene families due to their short length, and therefore were excluded from further analysis in that manuscript.…”
Section: Resultsmentioning
confidence: 99%
“…Microarray studies have shown novel aspects of immunity of particular species of molluscs. For example, different strains of the gastropod B. glabrata display distinct baseline expression profiles (Lockyer et al, 2012, 2008; Zahoor et al, 2014); this snail mounts pathogen-specific immune responses to Gram (−), Gram (+) bacteria and metazoan parasites (Adema et al, 2010), and FREP3 was identified as a common feature of successful defense responses (Hanington et al, 2012, 2010). …”
Section: Beyond “Factorology” Immunogenomics Phasementioning
confidence: 99%
“…At the cellular level, the snail's defense strategies include phagocytosis and cellular encapsulation of pathogens, while humoral factors include lectins, the production of oxygen radicals and a recently identified family of fibrinogen-related proteins (FREPs) (Yoshino and Coustau, 2011). These defense mechanisms likely involve changes in gene expression, and several studies show that the transcriptional profile of B. glabrata is modified in response to stressors such as gram-negative and gram-positive bacteria, mechanical wounding, and metazoan parasites Hanelt et al, 2008;Hanington et al, 2010;Ittiprasert et al, 2010;Lockyer et al, 2012;Mitta et al, 2005;Zahoor et al, 2014). Despite ample evidence of altered gene expression during immune responses in B. glabrata, the regulatory mechanisms responsible are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Despite ample evidence of altered gene expression during immune responses in B. glabrata, the regulatory mechanisms responsible are not known. Transcription factors have only recently been identified in B. glabrata (Bouton et al, 2005;Kaur et al, 2015;Zhang and Coultas, 2011) and just one promoter region has ever been characterized (Yoshino et al, 1998).…”
Section: Introductionmentioning
confidence: 99%